Growth performance, intestinal morphology, and carcass traits in broiler chicken fed Conocarpus erectus leaf meal - M. F. Al-qazzaz; A. M. Humam; H. A. AI- Mashhadani; O. A. Aljumaili; H. N. Ezzat (Journal of the Indonesian Tropical Animal Agriculture, 2023)
This study evaluated the effects of adding Conocarpus erectus leaf meal to the diet on the perfor-mance, carcass traits, organ weights, and intestinal morphology of broiler chicken. A total of 396 one-day-old Ross 308 broilers were assigned to nine treatments, which included 0, 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, and 2% C. erectus leaf meal addition to the broiler diet. Feed and bird weights were recorded weekly. On slaughter day, the weights of carcasses and organs were individual-ly reported using a digital scale as well as the intestine samples were pooled for tissue analysis. High levels of C. erectus leaf meal reduced (P<0.01) body weight, body weight gain, and feed conversion ratio. The basal diet and 0.25% C. erectus leaf meal diet reported higher (P<0.01) body weight and body weight gain than did the other treatments. Birds fed 0.25% C. erectus leaf meal supplementation performed similarly to those fed the basal diet. Significantly, with increasing amounts of C. erectus leaf meal in the diets, there was a linear slope decrease in live weight and body weight gain as well as a linear slope rise in the values of feed intake and feed conversion ratio. Carcass trait and relative organ weights were not altered among the dietary treatments. Feeding 1% C. erectus leaf meal diet decreased (P<0.01) relative abdominal fat weight compared to birds fed the control diet. Birds fed dietary C. erectus treatments had higher (P<0.01) villus height, villus width, crypt depth, and lower villus height/crypt depth ratio than did birds fed the control diet. In conclusion, the study indicated that feeding 0.25% C. erectus leaf meal showed no deleterious effects on the growth performance of the broiler. Growth performance and intestinal morphology were linearly reduced when broilers were fed up 2% of C. erectus meal.